The Relationship of Workload and Job Stress in Nurses in the Patient Room - Sukesi, Niken; Listiyani, Novi; Winarti, Rahayu; Wahyuningsih, Wahyuningsih (East Asian Journal of Multidisciplinary Research, 2024)
Workload from the difference between the workload of printers maximum load capacity of a person this motivated. Will result in excessive workload of the stress. Work stress refers to the feeling of strain that experienced employees feel in relation to their work. The aim of the study is to examine workload and work stress among nurses in a hospital nursing unit. The study is descriptive in nature with a cross-sectional approach. Research is a nurse at Kendal Hospital in Indonesia. The variables of this research is workload and job stress. The questionnaire workload is 13 questions with the reliability and validity of less than 0.05 0.827. The work stress questionnaire has 18 questions with validity test <0.022 and reliability test 0.760. The results of the study on the relationship between workload and work stress showed a value of 0.383 > 0.05, which means that there is no relationship between workload and stress of a nurse admitted to Kendal Hospital Room Hospital in Indonesia.